2021
DOI: 10.2147/nss.s307904
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Insomnia Among Truck Drivers in Japan

Abstract: Truck drivers with insomnia are at a high risk of traffic accidents. We aimed to investigate the prevalence of insomnia and identify its associated factors among truck drivers in Japan. Methods: Participants were 2927 male truck drivers younger than 65 years old. Selfadministered questionnaires were used to assess insomnia symptoms, State-Trait Anxiety Inventory, drinking, smoking habits, body mass index, caffeine intake, as well as daily driving hours, consecutive days away from home, and driving distance. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…However, the issues surrounding driving safety associated with insomnia have not received widespread attention. Previous works have shown that insomnia can cause cognitive dysfunction and is especially likely to impair the cognitive domains of vigilance, attention, and reaction time, which in turn can affect an individual’s daytime functioning and behaviors, including cognitively demanding driving behaviors ( Léger et al, 2006 ; Jeon et al, 2014 ; Miyachi et al, 2021 ). Ahlström et al found that sleep-deprived participants showed low lambda responses, which led to a general decline in cortical responsiveness to incoming visual stimuli; furthermore, low lambda responses were also associated with more line crossings while driving ( Ahlström et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the issues surrounding driving safety associated with insomnia have not received widespread attention. Previous works have shown that insomnia can cause cognitive dysfunction and is especially likely to impair the cognitive domains of vigilance, attention, and reaction time, which in turn can affect an individual’s daytime functioning and behaviors, including cognitively demanding driving behaviors ( Léger et al, 2006 ; Jeon et al, 2014 ; Miyachi et al, 2021 ). Ahlström et al found that sleep-deprived participants showed low lambda responses, which led to a general decline in cortical responsiveness to incoming visual stimuli; furthermore, low lambda responses were also associated with more line crossings while driving ( Ahlström et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%